Cervical Dilation at the Time of Epidural Catheter Insertion Is Not Associated With the Degree of Prolongation of the First or Second Stages of Labor, or the Rate of Instrumental Vaginal Delivery. Issue 2 (24th June 2021) - Lipschuetz, M.; Nir, E.A.; Cohen, S.M.; Guedalia, J.; Hochler, H.; Amsalem, H.; Karavani, G.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:1039–1049) Although epidural analgesia (EA) is used in over 60% of deliveries in Western countries with high patient satisfaction, it has been associated with risk of prolonged second stage of labor and instrumental vaginal delivery. The optimal time to administer EA based on cervical dilation is unknown, and whether the timing of its administration affects the duration of the first and second stages of labor or maternal or fetal outcomes. The aim of this study was to determine if the cervical dilation at the time of epidural placement impacts the duration of the first and/or second stage of labor and correlates with the rate of instrumental vaginal delivery.